Digital skills - Sánchez Medina, Irlesa Indira (2024)
The article reveals a research process that has achieved significant advances in the development of digital competencies, implementing innovative strategies that combine the use of various software tools with the personalization of teaching processes through the VARK model. Likewise, the preliminary results indicate a substantial improvement in the digital skills of the students, evidenced as strengthening this pedagogical approach.